PENGAWASAN ANGGARAN DITINJAU DARI BUDAYA LOKAL MAKASSAR DALAM KONSEP GOOD GOVERNANCE - Sucipto Rahman, Muh Nur; Nassaruddin, Fadliah; Lannai, Darwis (Invoice : Jurnal Ilmu Akuntansi, 2021)
The purpose of this study is to determine the correlation between good governance and siri 'napacce in guarding the realization of village funds and to know the application of culture and local wisdom of siri' napacce in carrying out their duties and responsibilities as village officials in Pacellekang Village, Pattallassang District, Gowa Regency.This research is a qualitative research with an ethnographic approach. The data source of this study is primary data in the form of direct interviews to several informants and subjects in the form of data from the research location. Furthermore, the data collection methods used were in-depth interviews, documentation and recording. Then, data processing and analysis techniques are qualitative analysis by building conclusions with the stages of data collection, triangulation data analysis and final conclusions.The results of this study indicate that the supervision of ADD management in Pacellekang Village is already good, in accordance with the principles of good governance. Starting at the planning stage, the implementation stage, and the accountability stage, the administration and financial management processes have been implemented in accordance with the principles of good governance, although there are still a few shortcomings. In addition, accountability and reporting are also direct to interested parties based on the cultural values of siri 'na pacce which can increase supervision of village fund allocation management (ADD) because as it is known that those who can participate in monitoring other than the community, the central government, are ourselves.Keywords: Supervision , Honesty, Village Fund Allocation, Siri 'na Pacce